Case-Control Pilot Study on Acute Diarrheal Disease in a Geographically Defined Pediatric Population in a Middle Income Country. (10th August 2017) - Farfán-García, Ana E.; Zhang, Chengxian; Imdad, Aamer; Arias-Guerrero, Monica Y.; Sánchez-Alvarez, Nayibe T.; Shah, Rikhil; Iqbal, Junaid; Tamborski, Maria E.; Gómez-Duarte, Oscar G.
Abstract : Introduction. Acute diarrheal disease (ADD) is a common cause of morbidity and mortality in children under 5 years of age. Understanding of the etiology of ADD is lacking in most low and middle income countries because reference laboratories detect limited number of pathogens . The objective of this study was to determine the feasibility to conduct a comprehensive case-control study to survey diarrheal pathogens among children with and without moderate-to-severe ADD. Materials and Methods. Microbiology and molecular-based techniques were used to detect viral, bacterial, and parasitic enteropathogens. The study was conducted in Bucaramanga, Colombia, after Institutional Review Board approval was obtained. Results. Ninety children less than 5 years of age were recruited after a written informed consent was obtained from parents or guardians. Forty-five subjects served as cases with ADD and 45 as controls. Thirty-six subjects out of 90 (40.0%) were positive for at least one enteropathogen, that is, 20 (44.4%) cases and 16 (35.5%) controls. Conclusions. The three most common enteric pathogens were enteroaggregative E. coli (10.0%), Norovirus (6.7%), and Salmonella spp. (5.6%). The E. coli pathogens were 18.8% of all infections making them the most frequent pathogens. Half of ADD cases were negative for any pathogens.